2015 IEEE International Conference on Information Reuse and Integration 2015
DOI: 10.1109/iri.2015.57
|View full text |Cite
|
Sign up to set email alerts
|

On Finding Explicit Rules for Personalized Forecasting of Obstructive Sleep Apnea Episodes

Abstract: Obstructive Sleep Apnea (OSA) is a breathing disorder that takes place during sleep, and has both short-as well as long-term consequences on patient's health. Real-time monitoring for a patient can be carried out by making use of ElectroCardioGraphy (ECG) recordings. This paper introduces a methodology to forecast OSA events in the minutes following the current time instant. This is accomplished by using a tool based on Differential Evolution that is able to automatically extract offline knowledge about the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…As changes in cardiac activity are expected to be more profound during respiratory events than in lead time duration, it is reasonable that pre‐90 segments performed worst among the pre‐OSA segments, as they were furthest from the respiratory events. Interestingly, we found that pre‐60 segments seemed to perform better than pre‐30 segments, contrary to our expectation that the performance would improve as segments got closer to a respiratory event as in other studies (Falco et al, 2015; Nasifoglu & Eroğul, 2021; Waxman et al, 2010). A possible explanation for this observation is that pre‐30 segments lay under CPAP effects in normalising the patient's respiration, as CPAP pressure opens the upper airway and normalises the cardiac activity (Karasulu et al, 2010; Kufoy et al, 2012).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…As changes in cardiac activity are expected to be more profound during respiratory events than in lead time duration, it is reasonable that pre‐90 segments performed worst among the pre‐OSA segments, as they were furthest from the respiratory events. Interestingly, we found that pre‐60 segments seemed to perform better than pre‐30 segments, contrary to our expectation that the performance would improve as segments got closer to a respiratory event as in other studies (Falco et al, 2015; Nasifoglu & Eroğul, 2021; Waxman et al, 2010). A possible explanation for this observation is that pre‐30 segments lay under CPAP effects in normalising the patient's respiration, as CPAP pressure opens the upper airway and normalises the cardiac activity (Karasulu et al, 2010; Kufoy et al, 2012).…”
Section: Discussioncontrasting
confidence: 99%
“…To address this issue, the current study aims to develop a novel machine-learning model for the early detection of sleep apnea events using single-lead electrocardiogram (ECG) signals. Inspired by the work of De Falco (Falco et al, 2015) and Huseyin Nasifoglu and Osman Erogul (Nasifoglu & Ero gul, 2021), we hypothesised that the changes in respiratory patterns could impact the autonomic nervous activity even before actual respiratory events occur, leading to alterations in ECG signals. ECG signals present a more convenient, less intrusive, and widely available alternative to respiratory flow trace across various clinical or home-based settings.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to these results, automatic feature extraction with a CNN model promises to be a more efficient method of predicting OSA events. De Falco et al extracted heart rate variability (HRV) features from 35 subjects and classification with a set of IF-THEN rules resulted in an average accuracy of 84.26%, sensitivity of 84.70%, specificity of 81.17% [27]. However, the database was annotated for each 1-minute segments, and only checks for whether an apnea occurs within that period or not.…”
Section: Discussionmentioning
confidence: 99%
“…De Falco et al proposed a model to predict an OSA episode in the next minute, based on the information obtained from the last three minutes intervals. IF-THEN rules are applied for the development of the algorithm from heart rate variability parameters of 35 subjects [27]. Maali and Al-Jumaily compared three types of neural networks (Elman, radial basis function and feed-forward back propagation) for various lead times [28].…”
Section: Introductionmentioning
confidence: 99%
“…The prediction system obtained best results using 30 s segments to predict events up to 30 s in advance. De Falco et al (2015) proposed a model to predict an OSA episode in the next minute, based on the information obtained from the last three minutes intervals. IF-THEN rules are applied for the development of the algorithm from HRV parameters of 35 subjects.…”
Section: Introductionmentioning
confidence: 99%